The implementation of contingency management intervention in an institutionalized drugs treatment facility in Malaysia - Abdul Ghani, Mohamad Salleh; Lim Abdullah, Haslee Sharil; Amat, Mohamad Isa (Human Resource Management Academic Research Society, 2022)
Despite Contingency Management Intervention (CM) having been proven to be a highly effective intervention in the context of substance use treatment and rehabilitation worldwide, it is still rarely studied in the context of institutionalized treatment settings. The purpose of the study was to determine the effectiveness of CM intervention conducted in an institutionalized drug treatment setting in Malaysia. The study’s main objective was to examine the effectiveness of CM intervention on clients’ treatment engagement within a usual psychosocial (PS) program. A total of 44 clients from the Narcotic Addiction Rehabilitation Centre or PUSPEN were randomly assigned into two groups, namely the experimental group and the control group. The experimental group followed a 12-week psychosocial intervention (PS) with CM intervention (CM) (PS+CM). Meanwhile, the controlled group inclusively went through 12 weeks of the usual psychosocial intervention program (PS). CM intervention was used to reinforce clients’ engagement within treatment sessions by giving tangible rewards for every treatment engagement behaviour recorded. Rewards collected have an associated monetary value which was used to redeem retail items such as food, toiletries, books and clothing items. Data collection was performed weekly for every psychosocial session conducted by the PUSPEN’s treatment officers. The findings demonstrated that CM intervention effectively improves clients’ treatment engagement and verified that CM interventions can also be conducted in an institutionalized drug treatment setting in Malaysia.